Pemanfaatan Teknologi Digital Bagi Masyarakat Kabupaten Takalar; Strategi Literasi Digital - Sangkala Sirate, Sitti Fatimah; Tasni, Nurfaida; Qalbi, Nur; Patiung, Naomi; Sapaan, Amika (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The presence of technology in the community, especially for farmers, can increase access to information, such as information about better and up-to-date agricultural techniques and market information will greatly help farmers in improving the quality and quantity of production that will encourage village economic growth and farmer welfare. The method used in the implementation of PKM activities uses an interactive discussion method with the local farming community accompanied by practice, a kind of tutorial in utilizing various mobile phone features owned by the community. The result of this study is that people know about how to upload images of agricultural production and market them through their social media, including accessing several marketplace links that allow people to market their agricultural products.